Rescue of common and rare exon 2 skipping variants of the GAA gene using modified U1 snRNA - Paolo Peruzzo; Natascha Bergamin; Martina Bon; Sara Cappelli; Alessandra Longo; Elisa Goina; Cristiana Stuani; Emanuele Buratti; Andrea Dardis (Molecular Medicine)
Abstract Background Pompe disease (PD) is an autosomal recessive lysosomal storage disorder caused by the deficient activity of acid alpha glucosidase (GAA) enzyme due to mutations in the GAA gene. As a result, undigested glycogen accumulates within lysosomes causing their dysfunction. From a clinical point of view, the disease can be classified in infantile-onset (IO) and late-onset (LO) forms. The common GAA c.-32-13T>G variant, found in 40–70% of LO-PD alleles, is a leaky splicing mutation interfering with the correct GAA exon 2 recognition by the spliceosome leading to the production of non-functional GAA transcripts. In this study, we used modified, GAA-tailored U1 snRNAs to correct the aberrant splicing determined by the c.-32-13T>G and other GAA exon 2-skipping mutations. Methods A set of constructs expressing 5 different engineered U1 snRNAs was generated. A functional splicing assay using a GAA hybrid minigene carrying different variants known to affect GAA exon 2 splicing was used to test the effect of engineered U1 snRNAs on exon 2 inclusion. The effect on endogenously expressed GAA transcript and GAA enzymatic activity was assessed by transfecting patient-derived fibroblasts bearing the common c.-32-13T>G with the best performing modified U1 snRNA. Results Modified U1-3, U1+1 and U1+6 snRNAs were all able to increase, in a dose-dependent manner, the inclusion of exon 2 within the transcript derived from the GAA minigene harbouring the c.-32-13T>G variant. The U1+1 was the most effective one (2,5 fold increase). Moreover, U1+1 snRNA partially rescued the correct splicing of GAA minigenes harbouring mutations that affect the 3’ss (c.-32-3C>G, c.-32-2A>G) and the 5’ss (c.546G>A, c.546G>C, c.546G>T). Notably, the treatment of patient-derived fibroblasts carrying the c.-32-13T>G mutation with the U1+1 snRNA increased the amount of normal GAA mRNA by 1,8 fold and the GAA enzymatic activity by 70%. Conclusions we provide the proof-of-concept for the use of modified GAA-tailored U1 snRNAs, designed to potentiate the recognition of the GAA exon 2 5’ss, as therapeutic tools to correct the aberrant transcripts carrying variants that affect exon 2 splicing, including the common c.-32-13T>G variant.